Implementasi Pembangunan Zona Integritas di Banten Berdasarkan Peraturan Menteri Hukum dan HAM Nomor 29 Tahun 2019 tentang Pembangunan Zona Integritas Menuju WBK dan WBBM - Lisa Rachmawati; Nurikah Nurikah; Rila Kusumaningsih (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2023)
The bureaucracy in this developing country has not positioned itself as a good servant to the community. Maladministration that often occurs in the realm of government makes the bureaucracy in Indonesia bad. The number of corrupt practices in public services encourages the government to be more active in bringing up various regulations in the wrong bureaucracy with the issuance of Minister of Law and Human Rights Regulation Number 29 of 2019 concerning the development of integrity zones towards WBK and WBBM. The zone of integrity is a renewal of good governance for transparency and accountability in the government realm as an effort to prevent acts of corruption, collusion and nepotism. The method used in this research is the empirical juridical method. Specifications of descriptive analytical research. The data source uses primary data and is supported by secondary data consisting of primary, secondary and tertiary legal materials. Data collection techniques in this study by means of interviews. The data obtained were analyzed descriptively with a qualitative data analysis approach. The theory used in this study is the theory of good governance and the theory of law enforcement. The results of the research regarding the implementation of the development of the integrity zone towards WBK/WBBM in the Ministry of Law and Human Rights of the Banten Regional Office in six areas of change have been implemented. The supporting factors include the commitment of the leadership and staff that looks very strong, and the inhibiting factors include weak supervision, lack of IT human resources in making public service innovations. In conclusion, with the implementation of the construction of the integrity zone as an improvement in the quality of public services as a form of obtaining the WBK and WBBM predicates